Book Reviews / Рецензии книг / Buchbesprechungen - Bakalova, Marina; Aguilar, Darling Pérez; Beuchling, Olaf (International Dialogues on Education Journal, 2014)
Olaf Beuchling (2012): Bildung als Adaptation? John U. Ogbu und der kulturökologische Ansatz der Minderheiten- und Sozialisationsforschung [¿La educación cómo adaptacíon? John U. Ogbu y la teoría ecológica-cultural sobre minorías y socialización]. Ryszard Kucha & Henryk Cudak (Eds.) (2013): European ideas in the work of famous educationalists. Internationalization, globalization and their impact on education. Vera Kaltwasser (2013): Achtsamkeit in der Schule. Stille-Inseln im Unterricht: Entspannung und Konzentration.